Pengenalan Perangkat Dan Sensor Secara Otomatis Menggunakan Metode Scanning Pada Komunikasi I2c - Noor ilmi; Agung Setia Budi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Currently, many vendors create products that make it easier for users to make IoT devices, especially sensors and microcontrollers. A sensor is an electronic device that can be used to sensing a situation around us and a microcontroller is used to help process data and as a communication line between sensors one and another. Because there are many different vendors, the more sensors are created and the more needs that use multiple sensors from different vendors are combined into one for a specific purpose. Therefore, something is needed to connect between various sensors from various vendors. sometimes has its own configuration. Based on this, a microcontroller is needed to bridge sensors to one another and can recognize these sensors automatically. And the communication line used is I2C (Intergrated Circuit) which is connected using SDA (Serial Data) and (Serial Clock) ). And from the results of testing the microcontroller is able to recognize the connected sensor.